The civic crime of corruption: Citizen networks and public sector bribery in the non-democracies - Zaloznaya, Marina (Theoretical criminology, 2022)
In the Global North, corruption is considered incompatible with civic health: scholars argue that it decreases social trust, atomizes communities, and discourages active citizenship. Using the first-ever national dataset from Russia with behavioral measures of corruption, ego-centric networks, and political participation, this article develops an alternative theory of corruption’s impact on civic life in societies where freedoms of association are limited. Analyses of these new data suggest that: (1) Russian bribe-givers are embedded in outward-oriented and mobilizable personal networks, supportive of civic connectivity; and (2) Russian bribe-givers are significantly more likely than law-abiding citizens to mobilize others when pushing back against the state. Counterintuitively, then, in non-democracies, corruption in the public sector sustains the kind of social networks that underlie civic culture.